Convergence Strategy of Radio Peduli in Parepare on Maintaining the Audience - Musrifah, Musrifah; Fitriana, A.Dian; Nurhakki, Nurhakki; Sahid, Muh (State Islamic Institute of Bone, Indonesia, 2024)
This article aims to understand the convergence strategy of Radio Peduli Parepare in retaining audiences, as well as knowing the obstacles and challenges of digitalization at Radio Peduli Parepare.The research method used is descriptive qualitative. Data collection techniques are observation, interviews and documentation. The data in this research was obtained from primary data and secondary data. This research uses media convergence theory, which focuses on the application of media convergence dimensions. These dimensions are ownership convergence, tactical convergence, structural convergence, information gathering convergence, and storytelling convergence. The research results show that 1). In media convergence there are five dimensions, however Radio Peduli Parepare only applies three dimensions of media convergence, namely, tactical convergence which at Radio Peduli Parepare has collaborated with online media by quoting or taking news from several online media that collaborate with the city government, structural convergence where Radio Peduli Parepare carries out restructuring or changes to its organizational structure almost every year, and storytelling convergence where Radio Peduli Parepare workers are able to present content through various social media platforms such as Facebook, Instagram, Twitter and YouTube. Apart from that, Radio Peduli also uses streaming applications such as erdio, my tuner radio, online radio box and radio.garden. 2). Radio Challenges: Concern about the lack of human resources, media competition with radio, which forces radio to converge and to sort and produce different news. Apart from that, the opportunity with media convergence is that you can use technology to reach listeners. Online streaming is easily accessed via the internet using various platforms such as Facebook, Instagram, YouTube and Twitter